Comparative analysis of meteorological performance of coupled chemistry-meteorology models in the context of AQMEII phase 2. (August 2015) - Brunner, Dominik; Savage, Nicholas; Jorba, Oriol; Eder, Brian; Giordano, Lea; Badia, Alba; Balzarini, Alessandra; Baró, Rocío; Bianconi, Roberto; Chemel, Charles; Curci, Gabriele; Forkel, Renate; et al.
Abstract: Air pollution simulations critically depend on the quality of the underlying meteorology. In phase 2 of the Air Quality Model Evaluation International Initiative (AQMEII-2), thirteen modeling groups from Europe and four groups from North America operating eight different regional coupled chemistry and meteorology models participated in a coordinated model evaluation exercise. Each group simulated the year 2010 for a domain covering either Europe or North America or both. Here were present an operational analysis of model performance with respect to key meteorological variables relevant for atmospheric chemistry processes and air quality. These parameters include temperature and wind speed at the surface and in the vertical profile, incoming solar radiation at the ground, precipitation, and planetary boundary layer heights. A similar analysis was performed during AQMEII phase 1 (Vautard et al., 2012 ) for offline air quality models not directly coupled to the meteorological model core as the model systems investigated here. Similar to phase 1, we found significant overpredictions of 10-m wind speeds by most models, more pronounced during night than during daytime. The seasonal evolution of temperature was well captured with monthly mean biases below 2 K over all domains. Solar incoming radiation, precipitation and PBL heights, on the other hand, showed significant spread between models and observations suggesting that major challenges still remain in the simulation of meteorological parameters relevant for air quality and for chemistry–climate interactions at the regional scale. Highlights: We evaluate the meteorological performance of coupled chemistry-meteorology models. 13 modeling groups from Europe and 4 groups from North America participated. Temperature, precipitation and radiation are mostly well simulated. Significant biases exist in surface wind speeds and nighttime boundary layer heights. Differences between model systems are usually larger than aerosol feedback effects.